PENGELOLAAN WISATA PANTAI BERDASARKAN KARAKTERISTIK DAN DAMPAK: STUDI KASUS PANTAI ANCOL DAN PANTAI KUTA - Frisda Sfarliana; Naufalika Anggy Zidany; Bangga Prameswara; Wiwik Dwi Pratiwi (Fakultas Seni Rupa dan Desain ITB, 2021)
Coastal tourism is a tourist activity based on natural attractions, which is vulnerable to the risk of environmental impacts.The study was conducted at two locations, namely, Kuta Beach and Ancol Beach, which are compared by using theintegrated management of coastal zones (ICM). The research was conducted by collecting secondary data in terms ofinformation taken from online news analized using qualitative approach. The results of the analysis show that there areseveral similarities and differences in how the integrated coastal management (ICM) is carried out according to thecharacteristics of the coastal typology and the environmental impacts